2020
DOI: 10.1088/1361-648x/ab6349
|View full text |Cite
|
Sign up to set email alerts
|

Gap-like feature observed in the non-magnetic topological insulators

Abstract: Non-magnetic gap at the Dirac point of topological insulators remains an open question in the field. Here, we present angle-resolved photoemission spectroscopy experiments performed on Cr-doped Bi 2 Se 3 and showed that the Dirac point is progressively buried by the bulk bands and a low spectral weight region in the vicinity of the Dirac point appears. These two mechanisms lead to spectral weight suppression region being mistakenly identified as an energy gap in earlier studies. We further calculated the band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, recent ARPES studies suggested that overlapping of impurity resonances with the Dirac node, a situation depicted in Fig. 1(b), could be achieved in the experiment as the binding energy of the node changes with increasing the film thickness 25 . It is also possible to resolve, at least partially, the impurity bands by adjusting the photon energy of the pulse.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, recent ARPES studies suggested that overlapping of impurity resonances with the Dirac node, a situation depicted in Fig. 1(b), could be achieved in the experiment as the binding energy of the node changes with increasing the film thickness 25 . It is also possible to resolve, at least partially, the impurity bands by adjusting the photon energy of the pulse.…”
Section: Discussionmentioning
confidence: 87%
“…Recent experiments indicate that favourable conditions can be achieved at least for some samples and dopants, e.g. for Cr in Bi 2 Se 3 above the magnetic ordering temperature 25 .…”
Section: Discussionmentioning
confidence: 99%